Wafer-scale reliable switching memory based on 2-dimensional layered organic–inorganic halide perovskite. Issue 40 (10th October 2017) - Seo, Ja-Young; Choi, Jaeho; Kim, Huo-Seon; Kim, Jaegyeom; Yang, June-Mo; Cuhadar, Can; Han, Ji Su; Kim, Seung-Joo; Lee, Donghwa; Jang, Ho Won; Park, Nam-Gyu
Abstract : 2D halide perovskite is promising material for reliable waferscale resistive memory even working at high temperature of 87 °C. Abstract : Recently, organic–inorganic halide perovskite (OHP) has been suggested as an alternative to oxides or chalcogenides in resistive switching memory devices due to low operating voltage, high ON/OFF ratio, and flexibility. The most studied OHP is 3-dimensional (3D) MAPbI3 . However, MAPbI3 often exhibits less reliable switching behavior probably due to the uncontrollable random formation of conducting filaments. Here, we report the resistive switching property of 2-dimensional (2D) OHP and compare switching characteristics depending on structural dimensionality. The dimensionality is controlled by changing the composition of BA2 MA n −1 Pb n I3 n +1 (BA = butylammonium, MA = methylammonium), where 2D is formed from n = 1, and 3D is formed from n = ∞. Quasi 2D compositions with n = 2 and 3 are also compared. Transition from a high resistance state (HRS) to a low resistance state (LRS) occurs at 0.25 × 10 6 V m −1 for 2D BA2 PbI4 film, which is lower than those for quasi 2D and 3D. Upon reducing the dimensionality from 3D to 2D, the ON/OFF ratio significantly increases from 10 2 to 10 7, which is mainly due to the decreased HRS current. A higher Schottky barrier and thermal activation energy are responsible for the low HRS current. We demonstrate for the first time reliable resistive switching from 4 inch wafer-scale BA2 PbI4 thin film working at both room temperature and a high temperature of 87 °C, which strongly suggests that 2D OHP is a promising candidate for resistive switching memory.